Self-assembled albumin nanoparticles induce pyroptosis for photodynamic/photothermal/immuno synergistic therapies in triple-negative breast cancer - Yang, Jianquan; Guo, Wen; Huang, Rong; Bian, Jiaojiao; Zhang, Siqi; Wei, Ting; He, Chuanshi; Hu, Ziyue; Li, Juan; Zhou, Chunyang; Lu, Man (Frontiers in Immunology, 2023)
Triple-negative breast cancer (TNBC) is characterized by a high degree of malignancy, early metastasis, limited treatment, and poor prognosis. Immunotherapy, as a new and most promising treatment for cancer, has limited efficacy in TNBC because of the immunosuppressive tumor microenvironment (TME). Inducing pyroptosis and activating the cyclic guanosine monophosphate-adenosine monophosphate synthase/interferon gene stimulator (cGAS/STING) signaling pathway to upregulate innate immunity have become an emerging strategy for enhancing tumor immunotherapy. In this study, albumin nanospheres were constructed with photosensitizer-IR780 encapsulated in the core and cGAS–STING agonists/H2S producer-ZnS loaded on the shell (named IR780-ZnS@HSA). In vitro, IR780-ZnS@HSA produced photothermal therapy (PTT) and photodynamic therapy (PDT) effects. In addition, it stimulated immunogenic cell death (ICD) and activated pyroptosis in tumor cells via the caspase-3–GSDME signaling pathway. IR780-ZnS@HSA also activated the cGAS–STING signaling pathway. The two pathways synergistically boost immune response. In vivo, IR780-ZnS@HSA + laser significantly inhibited tumor growth in 4T1 tumor-bearing mice and triggered an immune response, improving the efficacy of the anti-APD-L1 antibody (aPD-L1). In conclusion, IR780-ZnS@HSA, as a novel inducer of pyroptosis, can significantly inhibit tumor growth and improve the efficacy of aPD-L1.